The Drosophila ortholog of the endolysosomal membrane protein, endolyn, regulates cell proliferation. - Zhou, G; Zhang, Y; Ferguson, D; Chen, S; Rasmuson-Lestander, A; Campbell, F; Watt, S (2006)
Endolyn (CD164) is a sialomucin that regulates the proliferation, adhesion, and migration of human haematopoietic stem and progenitor cells. This molecule is predominately localized in endocytotic compartments, where it may contribute to endolysosomal biogenesis and trafficking. In order to more closely define the function of endolyn from an evolutionary view-point, we first analyzed endolyn orthologs in species ranging from insects, fish, and birds to mammals. The predicted molecular structures of the endolyn orthologs from these species are well conserved, particularly with respect to significant O-linked glycosylation of the extracellular domain, and the high degree of amino acid similarities within their transmembrane and cytoplasmic domains, with the latter possessing the lysosomal target signal, YXXphi. Focusing on Drosophila, our studies showed that the subcellular distribution of endolyn in non-polarized Drosophila S2 cells resembles that of its human counterpart in hematopoietic cells, with its predominant localization being within intracellular vesicles, while a small fraction occurs on the cell surface. Both Y --> A and L --> A mutations in the YHTL motif perturbed the normal subcellular distribution of Drosophila endolyn. Interestingly, embryonic and early larval development was often arrested in endolyn-deficient Drosophila mutants. This may partly be due to the role of endolyn in regulating cell proliferation, since knock-down of endolyn expression in S2 cells resulted in up to 50% inhibition of cell growth, with a proportion of cells undergoing apoptosis. Taken together, these results demonstrate that endolyn is an evolutionarily conserved sialomucin fundamentally involved in cell proliferation in both the human and Drosophila melanogaster.